Mem??rias, hist??ria de vida e introdu????o ?? obra de um educador - Gomes, Denise de Oliveira Campos Magalh??es (2009)
This work aimed to study the life and work of Professor Jos?? Eust??quio Rom??o. The central objective was to develop a biobliography of this character and militant in the history of Brazilian education. Valuing the memory as historical document, through the inter-relationship between oral and life history, biographical and bibliographical research , we tried to simultaneously link the character with its own production and both, author and work, included in a broader context, the socio-educational and the political. Based on the reminiscences, history of life and career development of Professor Rom??o, we thought on education and on the political contexts that involved it at some time, trying to know the educational scenery of the last fifty years in a broader manner. This study showed us an erudite man of orality dense, and with an early epistemological concern. An important public man and educator committed to striving for a free existence of the oppressed.